Pathogenetic Implications of BRAF Mutation Distribution in Stage IV Melanoma Patients - Baiter, Mirjam; Schuler, Gerold; Hartmann, Arndt; Schneider-Stock, Regine; Heinzerling, Lucie (Dermatology, 2015)
BRAF mutation frequencies in melanoma subtypes have clinical implications and offer pathogenetic clues.To characterize BRAF mutation status in melanoma of unknown primary (MUP) patients, in histological melanoma subtypes and by localization of primary tumors.In 179 patients with stage IV metastatic melanoma, BRAF mutation status, histological subtype and localization of primary (except for 29 MUP patients) were analyzed.BRAF mutations were found in 44.3%, of which 80.5% were BRAF V600E and 19.5% showed non-V600E BRAF mutations. BRAF mutation frequency depended on histological subtype (57.4% superficial spreading melanoma, 54.7% nodular melanoma, 11.1% mucosal melanoma, 28.6% acral lentiginous melanoma) and concerning non-V600E BRAF mutations on localization of primary. In MUP the BRAF mutation pattern resembled superficial spreading and nodular melanomas.BRAF mutation frequencies depend on histological subtype and localization of primary melanoma. Non-V600E BRAF mutations mostly occur in patients with primaries on 'head and neck' as well as 'trunk' but not on 'extremities'.
EVALuna2:6729